Acute Thoracic Aortic Dissection (Stanford Type B) Complicated with Acute Renal Failure. (12th November 2013) - Li, Li; Zhuang, ShunJiu; Qi, ShaoHong; Cui, JiaSheng; Zhou, JunWen; Zhu, Huaqi; Zhang, Wan; Li, Ming; Fu, Weiguo
Abstract : We report a recent case and review some literatures of acute aortic dissection (AAD) Stanford type B complicated with late onset of acute renal failure. The patient underwent preoperational peritoneal dialysis followed by thoracic endovascular aortic repair (TEVAR) and was fully recovered and discharged soon after surgery. We conclude that an AAD case is difficult to achieve a timely diagnosis, but with attention to systemic symptoms and dedication thorough treatment plan, a full recovery and positive prognosis are expected.